Grain storage and marketplace characteristics in Kebbi State, Nigeria - Hatzenbuehler, Patrick L.; Mavrotas, George; Maikasuwa, Mohammed Abubakar; Aliyu, Abdulrahaman; Bashir, Amina (International Food Policy Research Institute, 2018)
While there are many aspects to agricultural market modernization that are linked and mutually affect and reinforce each other, we argue in this paper that investment in Nigeria in physical market infrastructure, such as storage units, remains relatively neglected, especially in rural areas. That this is the case undermines successful agricultural development in the country. We examine the transactions cost, spatial market equilibrium, and industrial policy literatures to provide a conceptual context for understanding how and why investments in physical market infrastructure can lower transactions costs for traders and for farmers, and, thus, increase market participation. We also implemented a marketplace characteristics survey in Kebbi state, an agriculture-based state in northwestern Nigeria, to determine whether further investments in marketplace infrastructure are needed. We found that some markets, especially those in rural areas, lacked storage units and communications technologies. Hence, traders and farmers in those markets operate in a challenging environment. We argue that investments such as these are likely to be more successful in the long-run and have more immediate effects on local agricultural development than would national initiatives. Local governments have better knowledge of local conditions and can better design initial investments to strengthen markets and then implement follow-on initiatives required to meet needs that arise as market conditions evolve.